Experimental response of RC columns built with plain bars under unidirectional cyclic loading - Melo, J. (2012)
A large number of existing reinforced concrete (RC) buildings structures were designed and built before mid-70’s, when the reinforcing bars had plain surface and prior to the enforcement of the modern seismic-oriented design philosophies. This paper describes a series of unidirectional cyclic tests performed on seven full-scale columns built with plain reinforcing bars, without adequate reinforcement detailing for seismic demands. The specimens have different reinforcing steel details and different cross sections. A further monotonic test was also carried out for one of the specimens and an additional column, built with deformed bars, was cyclically tested for comparison with the results for the specimens with plain bars. The main experimental results are presented and discussed. The influence of bond properties on the column behaviour is evidenced by differences observed between the cyclic response of similar specimens with plain and deformed bars. The influence of reinforcement amount and displacement history on the column response is also investigated.